Strengthening of tribocoupling parts of transport and agricultural machines with fullerene materials - V.V. Aulin; A.A. Tykhyi; O. D. Derkach; S.V. Lysenko; D.O. Makarenko (Проблеми трибології)
The aim of this work is a comparative study of tribological properties and tribotechnical characteristics of polymer nanocomposites based on polyamide 6, modified with nanosized fillers. The work investigates polyamide 6 as a matrix modified with the following fillers: fulleroid materials (carbon fibers), microsized fillers containing nanoparticles (fullerene carbon black), nanoparticle fillers (fullerene C60).The influence of fulleroid modifiers and carbon fibers on the tribological properties of samples and parts made of polymer nanocomposites based on thermoplastic (polyamide 6) polymer matrices was studied. It was shown that the introduction of fulleroid modifiers allows to significantly reduce the friction coefficient of polymer compositions while increasing their mechanical characteristics. It was found that the use of carbon fibers for modification of polyamide 6 with an increase in mechanical characteristics during operation leads to an increase in the friction coefficient of the conjugated steel sample by more than two times compared to the original polymer matrix.